Evolução histórica e definições para a formação de um framework teórico sobre servitização - Rocha, Gustavo da Silva (Universidade do Vale do Rio dos Sinos, 2014)
The service bundling products has been a way differentiation and competition in the market, given that services are more difficult to imitate and can provide more long-term relationships with customers. Moving forward in this direction, there is the provision of integrated solutions with components of products and services. The process of aggregation services has been termed servitization and in some cases Product Service System (PSS). The servitization process requires skills and abilities of suppliers must be planned from the design phase. Design a solution requires consideration of product design on the design of bundled services and the design of solutions. This work aims to propose a theoretical framework to support servitization projects covering product design, product design and service design solutions. Specific objectives have: (i) examine the dichotomies and affections to the terms servitization concepts and its main synonym, PSS; (Ii) present the historical evolution of servitization and PSS checking the types of applications reported in the literature studied and the geographic location of the same. The literature search was the main method used. The analysis related to the topic of this research indicates that the articles servitization was first proposed in 1988. Several synonyms servitization were also identified as being present PSS. It was observed that the main cases in which companies servitization occurred in information technology, manufacturing and applications were for large companies like Apple, Xerox, Samsung. The theoretical framework proposed project servitization considered that servitization occurs initially in a stream where organizations focus primarily on manufactured products; the next stage, add some services; and the stage of offering solutions, deliver the whole package to the customer. Future research could conduct the validation of the framework with some managers and their implementation in any sector. This will be an important contribution because it can be constantly updated. Another future research would be to apply this framework both in different economic, social and cultural contexts in order to have a comparison of them. It would be possible to better assess the servitization process (solution) in different scenarios.
Keywords: Servitização; Serviço; Produto; Framework; Servitization; Service; Product; ACCNPQ::Engenharias::Engenharia de Produção